2012
DOI: 10.1371/journal.pone.0040146
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 Negatively Regulates Cytotoxicity in Exhausted CD8+ T Cells in HIV Infection

Abstract: Cytotoxic CD8 + T cells (CTLs) contain virus infections through the release of granules containing both perforin and granzymes. T cell ‘exhaustion’ is a hallmark of chronic persistent viral infections including HIV. The inhibitory regulatory molecule, T cell Immunoglobulin and Mucin domain containing 3 (Tim-3) is induced on HIV-specific T cells in chronic progressive infection. These Tim-3 expressing T cells are dysfunctional in terms of their capacities to proliferate or to produce cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 73 publications
4
68
1
Order By: Relevance
“…Consistent with the aforementioned immune control in the presence of phenotypically exhausted T-cells, there is evidence that PD-1 high CD8 + T-cells can express similar or even elevated levels of cytotoxic molecules compared to cells with a less pronounced exhausted phenotype 37,[42][43][44][45] .…”
Section: Evidence That Functional T-cells Are Maintained In Chronic Isupporting
confidence: 52%
See 1 more Smart Citation
“…Consistent with the aforementioned immune control in the presence of phenotypically exhausted T-cells, there is evidence that PD-1 high CD8 + T-cells can express similar or even elevated levels of cytotoxic molecules compared to cells with a less pronounced exhausted phenotype 37,[42][43][44][45] .…”
Section: Evidence That Functional T-cells Are Maintained In Chronic Isupporting
confidence: 52%
“… In vitro studies showed that the cytotoxic ability of HIV specific T-cells could be rescued by blocking Tim-3 45 .…”
Section: Malignant Diseasesmentioning
confidence: 99%
“…The resulting persistent antigen levels drive a process called "T cell exhaustion," whereby responding T cells undergo hierarchical loss of their effector functions, including their ability to proliferate, their cytotoxic potential, and their ability to produce cytokines (1). Coinhibitory molecules, including programmed death receptor 1 (PD-1) (2-6), lymphocyte activation gene-3 (LAG-3) (5,7,8), carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) (9)(10)(11)(12), and T cell immunoglobulin and mucin domain-containing protein 3 (Tim-3) (4,(12)(13)(14) contribute to T cell exhaustion, reducing potentially harmful, persistent T cell activation. However, this also results in suboptimal HIV-specific responses and ultimately poor control of the virus.…”
mentioning
confidence: 99%
“…Furthermore, while sTim-3 has been correlated with graft-versus-host disease (32), it is unknown whether it can modulate immune pathways. Given Tim-3's role in HIV-associated T cell dysfunction (12)(13)(14), sTim-3 might play a role in modulating T cell responses during HIV infection. However, it is unclear what role sTim-3 may play, and further, the functional properties of soluble receptors may be dependent on the type of construct produced.…”
mentioning
confidence: 99%
“…Due to the generation and transmission of costimulatory signals, the apoptosis of target cells can regulate the immune response artificially (14)(15)(16). Tim-3 might act as a ligand for reverse transmission of signals to affect tumor immunity correspondingly (17,18). In order to investigate this new mechanism of Tim-3 molecules, hepatoma Hepa1-6 cell strain of ICR mouse was used to build a solid tumor model in thigh muscle to study the inhibitory effect of Tim-3 molecule on Hepa1-6 solid tumor and the influence on immune system of tumor bearing ICR mice.…”
Section: Introductionmentioning
confidence: 99%